Saxifraga stolonifera inhibits porcine epidemic diarrhea virus infection by disrupting nucleocapsid protein-p53 interaction - Lu, Hongde; Liu, Haoyang; Guo, Ning; Zhou, Yu; Lu, Haiyan; He, Zhiyuan; Dong, Hong (Frontiers in Cellular and Infection Microbiology, 2025)
Porcine epidemic diarrhea (PED) is an acute, highly contagious intestinal disease caused by the porcine epidemic diarrhea virus (PEDV), which has devastating effects on the global swine industry. Currently, no effective therapeutic agents have been identified for treating PEDV infections. Saxifraga stolonifera (S. stolonifera), valued in traditional Chinese medicine for its anti-inflammatory properties, remains poorly studied regarding its efficacy against PEDV. This study demonstrated the dose-dependent inhibition of PEDV nucleocapsid expression by S. stolonifera in vitro. S. stolonifera strongly inhibited the expression levels of pro-inflammatory cytokines. Using the network pharmacology, key components such as gallic acid, quercetin, coumarin, and caffeic acid were identified. KEGG pathway enrichment analysis revealed that S. stolonifera mainly targeted pathways including p53, MAPK, and TNF to exert anti-PEDV effects. S. stolonifera treatment disrupted the interaction of PEDV N protein and p53. It also modulated the p53-DREAM signaling pathway by reducing p53 and p21 protein levels, while enhancing p130 (Ser672) phosphorylation, E2F4, and Cyclin A protein expression levels. Molecular docking revealed stable hydrogen bonding between the seven core components and the PEDV N protein, with quercetin exhibiting the lowest binding energy. Amino acid sequence analysis showed that quercetin and other components share conserved binding sites with the PEDV N protein. These findings underscore the potential of S. stolonifera as a natural antiviral agent against PEDV infection.